Cerebral malaria and epilepsy. - (:unkn) unknown (My University, 2008)
Malaria, one of the most common parasitic diseases worldwide, is responsible for more than one million deaths among African children every year. Its neurological form, known as cerebral malaria (CM) is a potential cause of epilepsy in malaria-endemic regions of the world, primarily made up for the most part by the sub-Saharan Africa. Herein, we review recent African studies that examine the association between CM and epilepsy. Three studies suggest a modestly strong association between CM and epilepsy. Furthermore, there appears little doubt that this association is causal. Speculative considerations that may explain this causal association are discussed in this review. Additional research is however required in order to determine the clinical and electrographic behavior, the underlying structural and molecular basis, and course and outcome of this condition.
Keywords: African Research